ETHICAL CONCERNS IN PLANT BIOTECHNOLOGICAL RESEARCH - Toms, Bini (Asian Horizons, 2013)
Plant biotechnology is a growing industry promising to offer remarkable economic, social and environmental advantages in the future. The figure below shows that in one decade, the worldwide grown area of transgenic or genetically modified (GM) crops has grown to 12.3 million hectares. Like other waves of change, biotechnology has evoked both praise and adverse reaction leading to a global debate over its potential for good or ill. The reactions whether good or otherwise are bound to be strong because the contents of discussion include food. Sustaining the revolution in plant biotechnology will require continued research on and careful thought about, the emerging ethical issues in this field.